ARTISTIC ANALYSIS OF THE MENTAL STATES PORTRAYAL IN THE NOVELS OF RAY BRADBURY AND ISAJON SULTAN - Yuldoshova, Shakhnoza (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
This article examines the artistic and psychological portrayal of internal states in Ray Bradbury's novels Fahrenheit 451 and Isajon Sultan's Eternal Wanderer, focusing on the characters' expressions. The study employs a psychoanalytic approach and comparative-typological methods. It examines the portrayal of spiritual growth and decline in the characters throughout the narrative, as well as the evolution of the protagonists' psyches, tracing their maturation through the challenges and contradictions they face and their spiritual growth and progress toward realization. In traditional works of fiction, the highest point of conflict in the plot is the climax, which reflects the impact of the dramatic action and is accompanied by the denouement, that is, the beginning of a decision or the reversal of a decision. These climaxes describe the characters' state of mind and internal changes. The study also considers the relationship between the characters' names and their roles in the work, their artistic skill, the author's philosophy, and the conflict between them.
Keywords: hero‘s psyche; inner states; realization; conflict; psychological analysis; character line; contrast